The Developments And Challenges Of Citizen Journalism In Indonesia - Sekar Arum Nuswantari; Puteri Alyasuci (Universitas Darussalam Gontor collaboration with ISKI (Ikatan Sarjana Ilmu Komunikasi Indo, 2023)
Citizen journalism arises because technology provides opportunities for consumers to become content producers, which can be referred to as user-generated content (UGC). With the emergence of the ability of citizens to produce content, citizen journalism has become an alternative to content produced by the mainstream media, especially after the presence of social media. In practice, citizen journalism will always go hand in hand with the mainstream media, which of course has bigger resources. Academic attention to citizen journalism has also developed from the beginning when this activity was formed until it developed into an alternative media for the public. The author focuses on previous studies, to be able to explain whether there are challenges behind the development of citizen journalism. This article is a literature review as a method, prioritizing articles collected from the accredited journal index system and the Google Scholar search engine. The results found that citizen journalism is still developing, both as an alternative media and as part of the mainstream media. However, in its development journalism has challenges in issues of ethics, law, accuracy, and reliability. The results of this study are expected to provide recommendations for future researchers related to ethics, law, accuracy, and reliability of citizen journalism.